PEMAHAMAN MASYARAKAT TENTANG PRODUK DAN OPERASIONAL PERBANKAN SYARI’AH DI PAMEKASAN - Sakinah --- (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2011)
Understanding of Society about Syari’Ah Banking still is minimum or less adequate. This matter is certainly influenced by some factors. This research aims to know the understanding of society about product and oprasional of Syari’Ah Banking in Pamekasan chosening location of Perumnas of Tlanakan Indah, village of Asem Manis, Countryside of Larangan Tokol, District Of Tlanakan, Sub- Province of Pamekasan. Result of research indicates that ( 1) Understanding of society perumnas of Tlnakan Indah about product and operational of Syari’Ah Banking is still very minimum. ( 2) Factors which influence caused some factors, for example, lack of information of side syari’ah banking and lack of understanding of society about religion teaching especially which touch with mu'amalah covered in Syari’Ah Banking.